2014
DOI: 10.1371/journal.pone.0108421
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Adipocyte Size with Adiposity and Metabolic Risk Factors in Asian Indians

Abstract: BackgroundEnlargement of adipocyte is associated with their dysfunction and alterations in metabolic functions.ObjectivesWe evaluated the association of adipocyte size of subcutaneous and omental adipose tissue with body composition and cardiovascular risk factors in Asian Indians.MethodologyEighty (40 males and 40 females) non-diabetic adult subjects undergoing elective abdominal surgery were included. Pre-surgery evaluation included anthropometric measurements, % body fat by bioimpedance, abdominal fat area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…In a sample of women ranging in adiposity from lean to moderately obese, after control for BMI, total BFM and visceral adipose tissue area measured by computed tomography, we found that OM FCS predicted triglyceride concentration whereas SC FCS did not 17 . Yet, in female and male Indians, another group reported no significant correlation between total cholesterol and triglyceride concentrations and SC or OM FCS after adjustment for BMI, BFM, waist circumference, total abdominal adipose tissue area and SC adipose tissue area 48 . However, in that particular study, associations between visceral adipose tissue accumulation and metabolic parameters were scarce as visceral adipose tissue only correlated with HDL-cholesterol and triglyceride concentrations in men.…”
Section: Blood Lipid Profilementioning
confidence: 97%
“…In a sample of women ranging in adiposity from lean to moderately obese, after control for BMI, total BFM and visceral adipose tissue area measured by computed tomography, we found that OM FCS predicted triglyceride concentration whereas SC FCS did not 17 . Yet, in female and male Indians, another group reported no significant correlation between total cholesterol and triglyceride concentrations and SC or OM FCS after adjustment for BMI, BFM, waist circumference, total abdominal adipose tissue area and SC adipose tissue area 48 . However, in that particular study, associations between visceral adipose tissue accumulation and metabolic parameters were scarce as visceral adipose tissue only correlated with HDL-cholesterol and triglyceride concentrations in men.…”
Section: Blood Lipid Profilementioning
confidence: 97%
“…In addition, Microarray Analysis showed that internal immune cell composition of high fat diet fed mice WAT was different with chow diet mice. On the other hand, this study also found in the initial stage of obesity, gonad VAT was firstly hypertrophy, next was SAT and mesenteric VAT [24]. Another research team carried out a similar experiment found that the increase of VAT fat volume was mainly caused by hypertrophy of adipocytes, while the increase of SAT was mainly achieved by cell proliferation [25].…”
Section: Discussionmentioning
confidence: 75%
“…O'Connell et al [15] reported that the size of human visceral adipocytes, but not of subcutaneous adipocytes, was strongly related to adiposity and metabolic risk factors. Meena et al [16] also indicated that the size of human visceral adipocytes was more closely related to the parameters of metabolic risk factors than was the size of subcutaneous adipocytes. In humans, visceral and intramuscular fat accumulations were more strongly associated with adiposity and the risk of metabolic syndrome than was subcutaneous fat growth [1e3].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of pref-1 decreased the inguinal adipose tissue weight with a reduction of inguinal adipocyte size in mice [14]. In addition, differences in adipocyte size are related to the parameters of metabolic risk factors in obese subjects [15,16]. However, it remains unclear whether the adipocyte size are related to the telomere length and/or to pref-1 gene expression in a fat depot-specific manner.…”
Section: Introductionmentioning
confidence: 99%